2019
DOI: 10.1111/cas.13888
|View full text |Cite
|
Sign up to set email alerts
|

Role of inhibitor of yes‐associated protein 1 in triple‐negative breast cancer with taxol‐based chemoresistance

Abstract: Triple‐negative breast cancer (TNBC) is highly clinically aggressive and taxol‐based chemoresistance remains a big TNBC therapeutic problem to be solved. Verteporfin, a small molecular yes‐associated protein 1 (YAP1) inhibitor, is little known as an antitumor drug for TNBC. Our data showed that YAP1 expression was associated with early relapse in tissue samples of patients with TNBC taxol chemoresistance (P < .001). Verteporfin reduced migration and enhanced apoptosis or autophagy of a taxol‐resistant MDA‐MB‐2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 23 publications
(36 reference statements)
1
24
0
Order By: Relevance
“…Originally, verteporfin was defined as a clinical photosensitizer and is an inhibitor of the YAP‐TEAD interaction . In previous reports, verteporfin without light activation was reported to exhibit cytotoxicity while suppressing the YAP pathway at a concentration of approximately 2–20 μ m (10–100 times higher than the concentration used in the current study) . In the present study, siRNA‐mediated knockdown of YAP did not reduce the MMP in GSCs, whereas verteporfin led to a reduction in the YAP‐knocked down GSCs.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…Originally, verteporfin was defined as a clinical photosensitizer and is an inhibitor of the YAP‐TEAD interaction . In previous reports, verteporfin without light activation was reported to exhibit cytotoxicity while suppressing the YAP pathway at a concentration of approximately 2–20 μ m (10–100 times higher than the concentration used in the current study) . In the present study, siRNA‐mediated knockdown of YAP did not reduce the MMP in GSCs, whereas verteporfin led to a reduction in the YAP‐knocked down GSCs.…”
Section: Discussionsupporting
confidence: 38%
“…We therefore screened drugs in clinical use for their ability to reduce MMP as an indicator and identified verteporfin (VPF, trade name Visudyne ® ), a Food and Drug Administration‐approved photoactivating drug that is used clinically for macular degeneration, as a candidate drug for targeting the OXPHOS in GSCs . Indeed, it has been reported that VPF suppresses cell proliferation and induces cell death of various cancer cells including glioblastoma cells as its side effect so far, but there is no report in GSCs . The medical effect of verteporfin is photoactivation‐dependent .…”
Section: Resultsmentioning
confidence: 99%
“…Having demonstrated that blocking SPHK1 activity attenuates BLM-or TGF-β-mediated mtROS and the expression of FN and α-SMA, we investigated the effect of YAP1 inhibition, or the downregulation of YAP1, with shRNA on mtROS, FN, and α-SMA expression in lung fibroblasts. The HLFs were pre-treated with YAP1 inhibitor verteporfin (1 µ M) [45,46] for 1 h prior to the TGF-β (5 ng/mL) challenge for 3 h, and mtROS was determined by MitoSOX. The inhibition of YAP1 by verteporfin reduced the TGF-β-induced mtROS ( Figure 8A), suggesting a role for YAP1 in mtROS production.…”
Section: Inhibition or Downregulation Of Yap1 Reduces Tgf-β-induced Mmentioning
confidence: 99%
“…CCK8 analysis revealed that the BT-549 cell line was the most sensitive to the inhibitory effect caused by VP on cell proliferation. VP treatment led to YAP, AXL, CYR61 and/or CTGF downregulation in the BC cell lines of different subtypes, suggesting that these effectors may act as their own target genes as described in MDA-MB-231 cells, VP could inhibit the transcriptional activity of TEAD, reduce the protein expression levels of YAP target genes, AXL and CTGF, inhibit the migration, and induce the apoptosis of paclitaxel resistant MDA-MB-231 cells [28][29][30]. The results of western blotting analysis proved that the protein and mRNA expressions of YAP, as well as of YAP targeted genes decreased along with the increase in the concentration of VP.…”
Section: Discussionmentioning
confidence: 83%